Strengthening the Porang Creative Economy through Value-Added Production and a Communal Integration Business Model - Dewati, Rosita; Setyarini, Agung; Harinta, Yos Wahyu; Arianti, Yoesti Silvana; Saputro, Wahyu Adhi (Universitas Panji Sakti, 2025)
Local food is a viable alternative to traditional food sources for meeting people's food needs. Central Java Province is a fairly high producer of porang. This is proven. One location with many farmers growing porang is in the buffer district of Surakarta City, namely Sukoharjo Regency. The production of food crops, especially porang in Sukoharjo, is what actually provides supplies to urban areas. Porang plants are sold in processed form, such as flour. The added value of this product increases economic value. The purpose of this study is to reveal the strengthening of the porang creative economy in Central Java Province through the creation of value-added products and the introduction of a communal business system that could potentially encourage porang production to become one of the iconic products in Central Java. This study uses a descriptive analytical method. This study utilizes primary data collected through direct interviews with farmers. The respondents of this study were 50 porang farmers in Sukoharjo Regency who are members of the Sukoharjo Porang Farmers' Friends (SPPS) in Kamal Village, Bulu District, Sukoharjo Regency. Data analysis used the Hayami method of value-added analysis and a literature review of the communal introduction system. The value-added analysis results show that glucomannan flour production generates an added value of IDR 199,641 per kg of porang tuber raw material with a ratio of 72.25%. The profit obtained by the trading business is IDR. 186,483 per kilogram of porang tuber raw material with a profit ratio of 68.68%. The communal introduction system enables the porang business to be well-managed, as there are still porang farmers outside Sukoharjo Regency who continue to plant. Communal integration can stabilize production supplies, thereby strengthening existing institutions and necessitating testing in the three districts involved.